Keragaman Hayati Agroekosistem Pisang (Musa sp.) di Jawa Barat - Muhamad Khais Prayoga; Ade Ismail (Composite : Jurnal Ilmu Pertanian, 2020)
Banana cropping patterns applied by farmers in West Java using polyculture systems. This system can build a diversity of plant species that are mutually beneficial. This study aims to determine the level of biodiversity of the banana ecosystem in West Java using vegetation analysis. The study was conducted in six districts in the area of ​​West Java (Garut, Purwakarta, Bandung, Cianjur, Bogor and Banjar) from February to April 2019. The materials used were all types of plants found in each observation location, while the tools used in the study this is the Global Positioning System (GPS), long meter, short meter, handcounter, digital camera, stationery. Observations using survey and exploration methods and location determination are done by purposive sampling. Vegetation analysis results show that West Java has a high level of biodiversity in annual crops and annual plants with diversity index values ​​of 2.66 and 2.83, respectively. Cassava (Manihot esculenta L.) became the most dominant annual crop in all plains with an important value index (INP) in the lowlands 86.62%, medium plains 58.32%, and in the highlands 57.22%. In the annual plants the dominant plants were coconut (Cocos nucifera) in the lowlands (INP = 42.31%), teak (Tectona grandis) in the medium data (INP = 35.79%) and mindi (Melia azedarach) in the highlands (INP = 54.28%).